PERAN LINGKUNGAN DALAM MENSTIMULASI PERKEMBANGAN BAHASA SERTA MENUMBUHKAN KARAKTER ANAK USIA DINI - Tia Salmah Paujiah; Heri Yusuf Muslihin; Taopik Rahman (PELANGI: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The environment is one of the factors that have high leverage in the development of language and children's character. Because with the environment children are able to carry out their routines well without experiencing any difficulties, especially in communicating. Similarly, the stimulus provided also affects the success of the child's character. character of early childhood, because siring with every good stimulus given to children it will also produce good character as well. The environment itself is divided into three parts, namely, the family environment, the school environment and the community environment. The research method used is library research.